Hasina's misrule and Bangladesh as a nation - Hasan, Md. Mahmudul (Media New Age Ltd., 2025)
In the aftermath of the 1919 Jallianwala Bagh massacre committed by the British, Nobel laureate Rabindranath Tagore returned his knighthood to the colonial government, stating: ‘The time has come when badges of honour make our shame glaring in the incongruous context of humiliation.’ Didn’t such a time ever come during the Hasina regime when an intellectual in Bangladesh needed to follow suit and relinquish their awards, honours, perks or privileges in protest against her misrule?